An integrated systems biology approach establishes arginine biosynthesis as a metabolic weakness in Candida albicans during host infection - Shuvechha Chakraborty; Indumathi Palanikumar; Yash Gune; K. V. Venkatesh; Karthik Raman; Susan Idicula-Thomas (Cell Communication and Signaling)
Abstract Candida albicans, responsible for approximately 70% of all Candida infections, is a leading cause of invasive candidiasis and poses a significant global health threat. With the emergence of drug-resistant strains, mortality rates have reached a staggering 63.6% in severe cases, complicating treatment options and demanding the discovery of novel therapeutic targets. To address this pressing need, using a unique multidisciplinary approach, we attempted to identify some the critical metabolic pathways that can be targeted to modulate the virulence of CAL. Condition-specific genome-scale metabolic models (GSMMs), along with a novel integrated host-CAL model developed in this study, highlighted the central role of arginine (Arg) metabolism and uncovered ALT1, an arginine biosynthesis enzyme, as a critical metabolic vulnerability in CAL virulence. Heightened expression of arginine biosynthesis genes indicated that increased arginine synthesis mainly occurred through proline intermediates during host interaction. Significantly impaired virulence and in vivo pathogenicity of ALT1-deleted CAL highlighted the potential of targeting arginine metabolism as a novel strategy to combat antifungal resistance and underscored the power of integrating systems biology with experimental approaches in identifying new therapeutic targets.